The elemental abundance of quiescent galaxies in the LEGA-C survey: the (non-)evolution of [α/Fe] from z = 0.75 to z = 0 - Bevacqua, Davide; Saracco, Paolo; La Barbera, Francesco; D’Ago, Giuseppe; De Propris, Roberto; Ferreras, Ignacio; Gallazzi, Anna; Pasquali, Anna; Spiniello, Chiara (Monthly notices of the Royal Astronomical Society, 2023)
We measure the [α/Fe] abundances for 183 quiescent galaxies at z = 0.60−0.75 with stellar masses ranging 10.4 ≤ log10(M*/M⊙) ≤ 11.6 selected from the Large Early Galaxy Astrophysics Census survey. We estimate [α/Fe] from the ratio of the spectral indices Mgb (λ ∼ 5177 Å) and Fe4383, compared to predictions of simple stellar population models. We find that 91 per cent of quiescents in our sample have supersolar [α/Fe], with an average value of [α/Fe] = +0.24 ± 0.01. We find no significant correlation between [α/Fe] and stellar metallicity, mass, velocity dispersion, and average formation time. Galaxies that formed the bulk of their stellar mass on time-scales shorter than 1 Gyr follow the same [α/Fe] distribution as those which formed on longer time-scales. In comparison to local early-type galaxies and to stacked spectra of quiescent galaxies at z = 0.38 and z = 0.07, we find that the average [α/Fe] has not changed between z = 0.75 and the present time. Our work shows that the vast majority of massive quiescent galaxies at z ∼ 0.7 are α-enhanced, and that no detectable evolution of the average [α/Fe] has taken place over the last ∼6.5 Gyr.
Veröffentlicht: 31. August 2023
Gesehen am 25.06.2024